1988
DOI: 10.1002/1097-0142(19880701)62:1<98::aid-cncr2820620118>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast-mediated osteolysis in bone metastasis from renal cell carcinoma

Abstract: Osteolytic characteristics of bone metastasis from renal cell carcinoma were morphologically and biochemically investigated. First, undecalcified ground sections of bone metastases were made from four patients with renal cell carcinoma. Second, renal cell carcinoma cell line (RCC-K1) was established from one of the four patients, and its effect on bone resorption in vitro was examined. Marked proliferation and activation of osteoclasts around the tumor cells was histologically demonstrated. Conditioned medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…In osteolytic metastases, osteoclasts play a key role in expanding the borders of metastatic nests (25,37,43). This is supported by histological observations demonstrating osteoclastic bone resorption (2,11,45), as well as by reports that the inhibited osteoclastic activities by the administration of bisphosphonate suppressed osteolysis and subsequent tumor expansion (22,37). As in physiological events, osteoblastic cells appear to regulate osteoclastic activity in the tumor nests through the receptor activator of nuclear factor-κB (RANK)/RANK ligand (RANKL) system (22).…”
Section: Methodsmentioning
confidence: 71%
“…In osteolytic metastases, osteoclasts play a key role in expanding the borders of metastatic nests (25,37,43). This is supported by histological observations demonstrating osteoclastic bone resorption (2,11,45), as well as by reports that the inhibited osteoclastic activities by the administration of bisphosphonate suppressed osteolysis and subsequent tumor expansion (22,37). As in physiological events, osteoblastic cells appear to regulate osteoclastic activity in the tumor nests through the receptor activator of nuclear factor-κB (RANK)/RANK ligand (RANKL) system (22).…”
Section: Methodsmentioning
confidence: 71%
“…Lastly, although we have provided evidence that MIP-1y may influence RBM-induced osteolysis through effects on bone-resorbing osteoclasts, MIP-1y may also have effects on bone-forming osteoblasts. Although evidence suggests that bone loss observed in RBM patients is mediated largely by increased bone destruction (10), reduced bone formation may also play a role. Because osteoblasts express both MIP-1y receptors Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that bone destruction caused by cancer is mediated by osteoclastic bone resorption rather than directly by tumour cells. 22 However, the mechanism underlying bone invasion remains poorly understood. Thus, the osteolytic model could be used as a reliable model reflecting the cancer-bone environment and has the advantage of accelerating the mechanical demonstration of bone metastasis.…”
Section: Discussionmentioning
confidence: 99%